Global patterns of phylogenetic beta diversity components in bats. (25th November 2013) - Peixoto, Franciele P.; Braga, Pedro Henrique P.; Cianciaruso, Marcus Vinicius; Diniz‐Filho, José Alexandre F.; Brito, Daniel; Daniel Kissling, W.
Abstract Aim To investigate global patterns of phylogenetic beta diversity (phylobetadiversity, PBD) components in bats (Chiroptera), testing whether the strong dispersal barriers among realms led to lineage differentiation between them and whether the flight capability of the study group created distance‐decay patterns in PBD, with lower turnover rates between the closest biogeographical regions. Location Global, delimited by biogeographical regions. Methods Using the global distribution of bats and a supertree available for most species, we calculated PBD using the complement of the PhyloSor index. In addition, to distinguish the relative roles of local (e.g. lineage filtering) and regional processes (e.g. speciation) in shaping broad‐scale patterns of PBD, we partitioned PBD into two components: the turnover component (PBDTurn) and the phylogenetic diversity (PD) component (PBDPD). We used a null model to test whether assemblages were more or less phylogenetically dissimilar than expected by chance. We also performed a Mantel analysis to analyse the distance‐decay patterns of PBD and its two components. Results The most striking difference in PBD was found between the Old World and the New World. In general, the PBD pattern was determined by PBDTurn. For some adjacent regions we noticed the PBDPD component was more important, indicating that the dissimilarity was mostly due to differences in phylogenetic diversity. On the other hand, for other adjacent regions, the observed PBDTurn was higher than expected by chance and the PBDPD was lower. This demonstrates that, although these regions are relatively close in space, there are other factors driving phylogenetic differences between them (i.e. ecological factors). Main conclusions Our results suggest that at broad scales, the PBD of bats is determined by PBDTurn. We postulate that the flight ability of bats led to low turnover rates between adjacent regions in the absence of other factors that can drive differences between them (e.g. strong environmental barriers).